(untitled) (Development Service Industry Management, 2025)
The research aims to clarify the nature of corporate security as a multidimensional phenomenon that combines economic, legal, informational, organizational, and social aspects, and to identify ways to enhance its role in ensuring the sustainable development of the agricultural sector. The article examines the processes of institutionalizing corporate security within the strategic management system of farming enterprises. It is determined that corporate security is a multidimensional management category that combines legal, economic, organizational, informational, and social elements, forming the basis for the sustainable functioning of the enterprise in the face of external challenges. It is substantiated that the institutionalization of corporate security involves its integration at all levels of strategic management – from planning and organization to motivation and control. This approach contributes to the formation of a single, risk-oriented management system, in which security is not treated as a separate function but as a component of the enterprise’s strategic potential. Corporate security, built into management, serves as a stabilizing factor that ensures the harmonious development of economic activity even under conditions of crisis or military threats. An approach is proposed in which corporate security serves as an indicator of management efficiency and an enterprise’s ability to adapt in a dynamic environment. Key risks inherent to agricultural structures include instability in the legal environment, vulnerability of logistics chains, cyber threats, personnel losses, and social tensions in rural communities. It is emphasized that in modern conditions of digitalization of the agricultural sector, corporate security also covers issues of data protection, intellectual property, compliance with compliance requirements, and reputational stability. The need to implement international security standards, in particular ISO 28000, as well as business continuity planning systems (Business Continuity Planning, BCP), to ensure the enterprise’s comprehensive resilience against internal and external threats, is emphasized. The development of a culture of corporate responsibility, transparency, and ethical management standards is identified as a key condition for increasing trust among investors and partners. The results of the study have practical significance for improving decision-making, increasing the efficiency of corporate control, and creating a safe environment for the development of agrarian business that combines economic performance with social sustainability.